PENGARUH PERSONALISASI POLITIK TERHADAP PEMILIH - Rambe, Ahmad Sampurna; Attaya, Muhammad Fairuz; Ibnuburrahman; Alfiris, Rizky Rahman; Lubis, Zakaria Musa (Algebra : Jurnal Pendidikan, Sosial dan Sains, 2025)
Political personalization is an increasingly dominant communication strategy in the practice of digital democracy, where the focus of politics shifts from institutions and ideologies to individual figures. This study aims to analyze the influence of political personalization on voter behavior, especially in the context of social media that allows direct and intense interaction between candidates and the public. Using a qualitative approach through literature study, this article examines how political personalization strategies are constructed and accepted by the public, as well as their impact on the quality of voter rationality. The results of the study show that voters, especially the younger generation, are more likely to respond to visual and emotional aspects of political figures such as communication style, personal narratives, and symbolic closeness on social media. Political personalization creates an impressive relationship between candidates and voters, but on the other hand also simplifies the complexity of politics into a contestation of personal images. The discussion shows that this phenomenon increases public involvement visually and emotionally, but reduces attention to ideas, programs, and policy substance. The conclusion of this study is that political personalization has a significant impact on shaping affective and impressive voter behavior, which in the long term can weaken the deliberative democracy process if not balanced by increasing public political literacy.